O16.6 General practitioner awareness of sexual orientation in a community and internet sample of gay and bisexual men in new zealand: implications for hpv vaccination. (13th September 2015) - Ludlam, AH; Saxton, PJ; Dickson, NP; Hughes, AJ
Abstract : Background: General practitioners (GPs) can improve HIV and sexually transmitted infection (STI) screening and advice for gay, bisexual and other men who have sex with men (GBM) if they are aware of a patient's sexual orientation. We aimed to estimate GP awareness of their GBM patients' sexual orientation and examine whether HIV and STI screening was associated with this. These data will also inform policy debates about targeted catch-up HPV vaccination strategies for adult GBM. Methods: We analysed anonymous self-completed data from 3168 GBM who participated in the community-based Gay Auckland Periodic Sex Survey (GAPSS) and internet-based Gay men's Online Sex Survey (GOSS) undertaken in New Zealand in 2014. Participants were asked if their usual GP was aware of their sexual orientation or that they had sex with men. Results: Half (50.5%) believed their usual GP was aware of their sexual orientation/behaviour, 17.0% were unsure, and 32.6% believed he/she was unaware. In multivariate analysis, GP awareness was significantly lower if the respondent was younger, Asian or an "other" ethnicity, bisexual-identified, had never had anal intercourse or had first done so very recently or later in life, and had fewer recent male sexual partners. GBM whose GP was aware of their sexual orientation were more likely to have ever had an HIV test (91.5% vs 57.9%; AOR 6.6), specific STI tests (91.7% vs 68.9%; AOR 4.6), and were twice as likely to have had an STI diagnosed. Conclusions: Lack of sexual orientation disclosure is resulting in missed opportunities to reduce sexual health inequalities for GBM. This is despite over 20 years of anti-discrimination law and near complete legal equality. To address this, general practices should provide more proactive, inclusive and safe environments for sexual orientation minorities. Uptake of HPV vaccination among sexually-active GBM will be suboptimal unless communication about sexual orientation with GPs improves.